10x-3y = 36

10x = 36 + 3y

x = 3.6 + .3y

substitute x into second equation 2+5=−4

2(3.6 + .3y) + 5y = -4

7.2 + .6y + 5y = -4

7.2 + 5.6y = -4

5.6y = -11.2

y = -2

substitute y into either equation 2x + 5y = -4

2x + 5(-2) = -4

2x - 10 = -4

2x = 6

x = 3

answer: x = 3, y = -2

10x = 36 + 3y

x = 3.6 + .3y

substitute x into second equation 2+5=−4

2(3.6 + .3y) + 5y = -4

7.2 + .6y + 5y = -4

7.2 + 5.6y = -4

5.6y = -11.2

y = -2

substitute y into either equation 2x + 5y = -4

2x + 5(-2) = -4

2x - 10 = -4

2x = 6

x = 3

answer: x = 3, y = -2